Rationale Selection Of Local Areas For Placing Small Recreational Facilities - Анісімов, С. В. (Man and Environment. Issues of Neoecology)
Purpose. The comprehensive assessment of the local recreational areas in the basin of Seversky Donets River within Kharkov region for prioritizing of development a summer short rest facilities without compromising the environment. Methods are based on the approach developed by the author, of prioritizing the development of recreational activities in the local areas, taking into account environmental and economic characteristics. Results. Designed classification and grading scale are the basis for assessing the resources and services of water bodies, forests, aesthetic appeal, territorial and transport accessibility of potential recreational areas. Comprehensive assessment, taking into account both natural and environmental and economic conditions of the territories, carried out for 6 plots in the coastal zone Seversky Donets River. Selecting areas was carried out taking into account the hydrographic, hydrological, climatic criteria and recreational demand. Conclusions. Based on the assessment were selected two local areas, the most promising for the placement of small recreational facilities.